Alphaea alfreda, a new species from China and Myanmar (Lepidoptera, Erebidae, Arctiinae - Volynkin, Anton V.; Saldaitis, Aidas (Zootaxa, 2019)
The arctiine genus Alphaea Walker, 1855 is distributed in North and North East India, Nepal, southern China and northern Indochina. The genus was recently reviewed by Dubatolov & Kishida (2005). It is subdivided into three subgenera, Alphaea, Flavalphaea Dubatolov & Kishida, 2005 and Nayaca Moore, 1979 and includes 10 valid species. During a lepidopterological expedition to the north-western part of China’s Yunnan Province in May of 2018, an undetermined species of Alphaea was collected. The Chinese specimens have the wing pattern very similar to that of A. (Flavalphaea) khasiana (Rothschild, 1910), but red and black abdomen (that is orange and black in A. khasiana).